Extraction and Characterization of Fractionated Cellulose from Acacia Senegal. Issue 15 (23rd November 2022) - Parihar, Deepika; Kumar, Maneesh; Gehlot, Praveen Singh; Surolia, Praveen K.; Prasad, Gayatri
ABSTRACT: The present study reports the extraction of cellulose from Acacia senegal by means of bleaching followed by alkali and acidic treatment. Isolated crude cellulose was further fractionated to obtain alpha (α) and beta (β) cellulose. The structural analysis was carried out by FTIR, CP-MASS 13 C-NMR, and XRD. The morphology and thermal stability were investigated by SEM and TGA, respectively. The yield of cellulose (crude) in Acacia senegal was reported as 47%, while the content of α and β fractions of crude cellulose were 88.5% and 6.3% respectively. That suggests the predominant presence of α-cellulose in Acacia senegal . The FTIR data confirms cellulose extraction and also showed that alkali and acidic treatment successfully removed most of the hemicellulose and lignin from cellulose. Through XRD assessment, the crystallinity index of β-cellulose (82.09%) was found to be greater than α-cellulose (67.96%) and crude cellulose (75.70%). TGA demonstrated remarkably high thermal stability of β-cellulose with significantly low thermal decomposition i.e., 1.94% up to 640°C. The high thermal stability can create a new opportunity for Acacia cellulose to use it as an effective reinforcement for the preparation of biocomposites. The findings of this study would be helpful for further studies to know their possible applications. Graphical Abstract: uf0001